THE PATTERN OF ABSORPTION OF ISLAMIC LAW INTO NATIONAL LAW: Study of The Halal Product Guarantee Law in The Perspective of Maqashid Shari’ah - Rohmah, Siti (Jurisdictie: Jurnal Hukum dan Syariah, 2021)
The transformation of Islamic Law into the Halal Product Guarantee or Jaminan Produk Halal (JPH) Law is unique. Muslim minorities in Indonesia worry that the JPH Law is no longer voluntary but mandatory. The state acts as a regulator and an operator at the same time. This is because the JPH Law is derived from Islamic law but is intended for both Muslim and non-Muslim producers, in national and international context. This research aims to analyze the pattern of absorption of Islamic law in the jurisprudence provisions of halal products into the JPH Law and to review it from the perspective of maqashid shari’ah. This is a normative juridical research with a qualitative approach. The results indicate that 1) there are two patterns of absorption. On one hand, its existence reflects the pattern of Islamization of national law. On the other hand, it reflects the pattern of nationalization of Islamic law; 2) in the perspective of maqashid shari’ah a) the pattern of Islamization of JPH into National law is an expression of preserving religion (hifdz al-din) and the realization of hifdzu al-’aql; b) the pattern of nationalization of Islamic law in the JPH Law is deemed appropriate, if it is related to the philosophical values contained in the pattern of absorption of Islamic law. This is because the nationalization of Islamic law is a pattern that emphasizes the absorption of Islamic legal values that are compatible with Indonesian culture. Transformasi Hukum Islam ke dalam Undang-Undang Jaminan Produk Halal memiliki keunikan tersendiri. Ada kekhawatiran bagi minoritas muslim di Indonesia jika aturan tersebut diberlakukan secara mandatory, tidak lagi voluntary. Negara bukan hanya berposisi sebagai regulator akan tetapi pada waktu yang bersamaan Negara juga berperan sebagai operator. Hal ini karena UU JPH yang bersumber dari hukum Islam namun diperuntukkan untuk semua produsen baik muslim maupun non muslim, baik dalam konteks nasional maupun internasional. Artikel ini bertujuan untuk menganalisis pola penyerapan hukum Islam yang ada dalam ketentuan fikih produk halal ke dalam UU JPH, serta meninjaunya dalam perspektif maqashid syari’ah. Metode penelitian adalah yuridis normatif dengan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa pola penyerapan hukum Islam ke dalam UU JPH memiliki dua pola, yaitu pola islamisasi hukum nasional dan juga mencerminkan pola nasionalisasi hukum Islam. Kajian dalam perspektif maqashid syari’ah, pola Islamisasi Jaminan Produk Halal ke dalam hukum Nasional merupakan ekspresi untuk menjaga kelestarian agama (hifdz al-din) dan terwujudnya hifdzu al-‘aql. Pola nasionalisasi hukum Islam dalam UU JPH dirasa tepat, jika dikaitkan dengan nilai-nilai filosofis dalam pola penyerapan hukum Islam yang menekankan pada penyerapan nilai-nilai hukum Islam yang kompatibel dengan kultur keindonesiaan.